The Relationship Between Self Control and FoMO (Fear of Missing Out) with Nomophobia in College Students - Abdi Wibowo, M. Ganda; Suroso; Pratitis, Niken Titi (Sinergi International Journal of Psychology, 2025)
Excessive smartphone use in the era of rapid technological advancement can lead to various negative impacts on life, including insomnia, addictive behaviors, nomophobia, impaired cognitive function, and other health and psychological issues. Strong self-control in individuals can mitigate the tendency to experience the fear of missing out FoMO. This study involved a sample of 115 students from state and private universities, as well as civil service or vocational schools in Surabaya. The population characteristics of this study included active students aged 17– 29 years in Surabaya. This quantitative research was analyzed using multiple regression tests and path analysis with the SPSS 16 IBM for Windows program. The results indicated a positive relationship between self-control and nomophobia among students. Specifically, the higher the level of self- control an individual possesses, the lower the level of nomophobia they experience. Additionally, the study found that FoMO mediates the relationship between self-control and nomophobia. Individuals with low self-control are more susceptible to FoMO, which in turn exacerbates their experience of nomophobia.